Competitiveness in the European consolidated banking sector after the 2008 financial crisis - Senanu Kwasi Klutse (Review of Economic Perspectives, 2020)
The constitutional conception of market integration within the European Union entails creating a level playing field for competition in the consolidated banking sector. The financial crisis of 2008 brought with it the need to proceed with care as it rolled back the gains of improving competitive conditions in the financial sector. Even though a lot of studies have investigated competitive conditions prior to the crisis, the same cannot be said of periods after the crisis. Using both structural and non-structural measures of competitive conditions, this study found that the consolidated banking sector in Europe shows signs of a monopolistic competitive market structure based on its revenue and cost measures. As five countries - United Kingdom, France, Germany, Spain, Italy - control about 70 per cent of total assets in the consolidated banking sector. The capital expense to fixed assets and total assets in the Europe area were found to be negatively related to measures of profitability in the sector. They were indicating that the accumulation of assets eats into the incomes of banks in the sub-region, whereas bank exposures may be affecting bank profits.
Keywords: G21; L12; L11; 330; Banks; Monopoly; Market Structure